PERMEABILITY OF CERVIX AND OPTIMAL TIMING OF FERTILIZATION IN PUBERTAL GILT - Usenko, S.O.; Shostya, A.M.; Polishchuk, A.A.; Moroz, O.Н.; Stoyanovsky, V.Н.; Karpovsky, V.I.; Bilash, S.M. (World of Medicine and Biology, 2018)
The article highlights the results of research on the features of cervix permeability and optimal periods of fertilization in pubertal gilt.Five high-yield boars of the large white breed, aged 18-36 months, were used in experiments and evaluated for the quality of sperm. The start of the estrus was carried out using a test boar.In the first attempt to establish the permeability of the cervical canal, 3 groups of large white breeds were formed for 15 heads in each, which were inseminated at the onset: of the first (1st group), the second (2nd group) and the third period f the estrus at the age of 6 - 8 months. Gilt were fertilized with a sperm dosage of 70 ml of a diluent containing 2 billion sperm.In the second experiment to determine the optimal timing of insemination, 66 gilt of large white breed aged 8 to 9 months, live weight 110-130 kg, with clear signs of the start of proestrus, estrus and diestrus were used.The beginning of the estrus was set twice a day at 7 o'clock and 19 o'clock. Spermodoses (2 billion sperm in 70 ml of diluent) were injected into the gilt according to the following scheme: Group I - after the prescribed period of the estrus - 0 hours; Group II - after 6 hours; III - group - 12 hours; Group IV - 18 hours; V - 24 hours; VI - 36 hours. It has been established that cervical permeability increases with age of gilt and the number of reproductive cycles.In gilt, in the first reproductive cycle, the permeability of the cervical canal is 4.61 cm and intensively increases twice: 1.9 (p
Keywords: reproductive cycle; estrus; cervix; fertilization; sperm; gilt